Chronic Pain Following Physical and Emotional Trauma: The Station Nightclub Fire - Egyhazi, Rachel; Fregni, Felipe; Bravo, Gabriela L.; Trinh, Nhi-Ha T.; Ryan, Colleen M.; Schneider, Jeffrey C. (Frontiers in Neurology, 2014)
Objective: The purpose of this study was to evaluate factors associated with chronic pain in survivors of a large fire, including those with and without burn injury. Methods: This study employed a survey-based cross-sectional design to evaluate data from survivors of The Station nightclub fire. The primary outcome measure was the presence and severity of pain. Multiple linear regressions with a stepwise approach were used to examine relationships among variables. Variables considered included age, gender, marital status, burn injury, total body surface area, skin graft, premorbid employment, time off work, return to same employment, depression (Beck Depression Inventory, BDI) and post-traumatic stress (Impact of Event Scale-Revised, IES-R). Results: Of 104 fire survivors, 27% reported pain at least 28 months after the event. Multiple factors associated with pain were assessed in the univariate analysis but only age (p = 0.012), graft (p = 0.009), and BDI score (p < 0.001) were significantly associated with pain in the multiple regression model. Discussion: A significant number of fire survivors with and without burn injuries experienced chronic pain. Depth of burn and depression were significantly associated with pain outcome. Pain management should address both physical and emotional risk factors in this population.